Pengaruh Media Sosial Terhadap Kesadaran Hukum Masyarakat Di Era Digital - ., Suandana (Belom Bahadat, 2025)
The development of digital technology has changed the patterns of communication and social interaction in society through the presence of social media. This study examines the influence of social media on public legal awareness in the digital era, highlighting its role as a means of disseminating legal information and its potential causes of declining compliance with legal norms. Using a qualitative descriptive approach, this study examines how social media can be an effective legal education tool when used wisely, but also has the potential to lead to legal violations if misused. The results show that social media has two opposing sides: on the one hand, it can increase public understanding and legal awareness, but on the other hand, it can lead to deviant behavior due to low digital and legal literacy. Therefore, increasing legal awareness through digital education and strengthening social media ethics are crucial to creating a law-abiding society in the digital era.